Intervalos de referência para sódio, cloreto e potássio em amostras urinárias isoladas - Ana Carla Campos dos Santos Botelho (2015)
Reference intervals are used in clinical practice as support for the interpretation of laboratory tests. However, some measured anayts lack reference intervals established in literature, such as sodium, chloride and potassium determined in spot urine (element/creatinine) that is traditionally done in 24h urine (mEq/24h). The objective of this study is to correlate the urinary excretion of these ions in the 24h urine with the spot urine for later establishment of reference intervals in these samples. This is a cross-sectional study composed of 99 healthy adults individuals Correlations between sodium (Na), chloride (Cl) and potassium (K) urinary excretions were calculated on spot samples and in 24h samples through Spearman's correlation coefficient for the definition of the most appropriate time for spot samples to be obtained. The reference intervals were later established according to the Clinical and Laboratory Standards Institute (CLSI) recommendations. From the correlation data, the urinary samples collected between 6am-9am after breakfast and between 6pm-9pm were chosen for the establishment of the reference intervals of urinary sodium and chloride. For the potassium, the only sample selected was the collected between 6pm-9pm, since the sample collected between 6am-9am did not correlated with the 24h urine. For the samples collected between 6am-9am, the reference intervals for the sodium and chloride were 29-268 mEq/g creatinine and 27-291 mEq/g creatinine, respectively. For the 6pm-9pm samples, sodium, chloride and potassium obtained the intervals of 40-325 mEq/g creatinine, 30-307 mEq/g creatinine and 12 and 81 mEq/g creatinine. In conclusion the sodium, potassium and chloride excretions in spot samples correlated with 24-h urine, enabling the establishment of their reference intervals.